OBTENCIÓN Y CARACTERIZACIÓN DE HARINA DE ARROZ PARA USO EN PRODUCTOS DE PASTELERÍA SIN GLÚTEN - Acuña Gómez, Ana Carolina
In the process of threshed rice obtained between 4 and 16% of broken grains, which are used for the brewing industry, pastes and feed. To generate an added value broken grain rice flour was developed for use in bakery products. This requires a methodology that allowed obtaining flour by the process of moisturization and conditioning grain, followed by a grinding process and subsequent drying to a moisture content of 14.47% was applied. Further,HE andlabored different prototypes, varying formulations the content of rice flour and wheat flour. Five products were made in relation50% -50% to 100% rice flour, being the most sensory preference the sample with 100% rice flour applying organoleptic evaluation attributes for color, odor, flavor and consistency. In conclusion, it is determined that the rice flour can be used as raw material for products free biscuits and pastry glúten generating a great alternative for food processing processes in a market of celiacs.